Dividend policy and shareholders' wealth of listed manufacturing companies in Sri Lanka - Balagobei, S.; Selvaratnam, P. (IISTE, 2015)
In finance, over the years impact of a firm’s dividend policy on shareholders’ wealth is an unresolved issue. The main issue of debate revolves around the optimal Dividend payout which is maximizing the Shareholders’ wealth of investors. The country’s manufacturing sector is enjoying a stronger pace in earnings growth post war in Sri Lanka. Therefore the necessity of manufacturing sector is realized for the country’s economical development. This study aims to investigate the impact of dividend policy on shareholders’ wealth of listed manufacturing companies in Sri Lanka. The common approach in empirical studies has been to examine the relationship between dividend policy and shareholders’ wealth. The sample of this study composed of twelve listed Manufacturing companies in Sri Lanka and period of five years from 2008 to 2012. The required data and information for the study were gathered from published annual reports and hand book of listed companies in CSE. The correlation and regression analysis were used for data analysis. The result of this study reveals that there is a significant relationship between the dividend policy and shareholders’ wealth and further dividend per share has a significant impact on shareholders’ wealth of listed manufacturing companies in Sri Lanka. Keywords: Dividend policy, Shareholders’ wealth, Dividend per share
Keywords: Dividend policy; Shareholders'wealth; Dividend per share